2010
DOI: 10.1016/j.jcrimjus.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Bad moon on the rise? Lunar cycles and incidents of crime

Abstract: a b s t r a c tPopular cultures in Western societies have long espoused the notion that phases of the moon influence human behavior. In particular, there is a common belief the full moon increases incidents of aberrant, deviant, and criminal behavior. Using police, astronomical, and weather data from a major southwestern American city, this study assessed whether lunar cycles related with rates of reported crime. The findings fail to support popular lore, which has suggested that lunar phase influenced the vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Foster and Roenneberg (2008) in their review paper cited 45 studies that found no consistent relationship between lunar influence and psychosis, depression, anxiety, violent behaviour, aggression, seizures, suicides, absenteeism rates, coronary failure, conception, birth, menstruation, surgery and survival of breast cancer, post-operative outcome, renal colic, outpatient admissions and automobile accidents. Schafer et al (2010) cited several additional studies in which no lunar effect was found on prison escapes, hospital admissions for dog bites, hockey player aggression and homicide. Margot (2015) showed that the few studies that found a relationship between the phase of the moon and the studied effect have typically made one of the following errors: small sample size, short period of study, lack of control for holidays or day of the week, cycle of the moon sampling procedure or statistical testing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Foster and Roenneberg (2008) in their review paper cited 45 studies that found no consistent relationship between lunar influence and psychosis, depression, anxiety, violent behaviour, aggression, seizures, suicides, absenteeism rates, coronary failure, conception, birth, menstruation, surgery and survival of breast cancer, post-operative outcome, renal colic, outpatient admissions and automobile accidents. Schafer et al (2010) cited several additional studies in which no lunar effect was found on prison escapes, hospital admissions for dog bites, hockey player aggression and homicide. Margot (2015) showed that the few studies that found a relationship between the phase of the moon and the studied effect have typically made one of the following errors: small sample size, short period of study, lack of control for holidays or day of the week, cycle of the moon sampling procedure or statistical testing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of the difficulty in obtaining data calibrated in daily or hourly intervals, prior research analyzed data drawn from a single geographical location (Núñez et al, 2002;Schafer et al, 2010). These types of samples are problematic because they tend to be unrepresentative thereby making generalizability of results difficult.…”
Section: Current Studymentioning
confidence: 99%
“…Thus, it is not necessary to include in the outdoor crime equation tangentially related control variables such as the amount of precipitation in a 24-h period, temperature, or weekend (see Schafer et al, 2010). These commonly used control variables are problematic because they tend to be vitiated with measurement error.…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the researchers did not control for variables that may influence the frequency of fatalities, e.g., temperature, day of week, precipitation, cloudy sky, etc. Other research generally provides unreliable evidence for the effect of lunar phase on reported crime and disorderly conduct (e.g., Núñez et al, 2002;Schafer et al, 2010). At least in terms of aggression or crime at nighttime, changes in the moon's illuminance do not generally support the opinion that as more light is reflected by the moon, visibility and deviant behavior increases.…”
Section: Introductionmentioning
confidence: 97%